Systemic inflammation partially mediates the association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and chronic cough - Changfen Wang; Xuecheng Liao; Jiulin Chen; Ying Lan; Jun Wen (Lipids in Health and Disease)
Abstract Background Non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR), a new biomarker, reflects blood lipid status. Nevertheless, the association between NHHR and chronic cough remains uncertain. Method This investigation included 9725 individuals from the NHANES. This research employed multiple statistical models to illustrate the association between NHHR and chronic cough. These models included logistic regression models, the Shapley Additive Explanations (SHAP) model, trend tests, mediation analysis, restricted cubic splines (RCS), and subgroup analyses. Result The logistic regression model, adjusting all covariables, showed a positive association between NHHR with chronic cough (OR: 1.08; 95% CI: 1.02–1.14). Trend tests and RCS further proved that NHHR and chronic cough had a linear and positive association. The mediation analysis proved that systemic immune inflammation index (SII) and systemic inflammatory response index (SIRI) partially mediated the association between NHHR and chronic cough. The SHAP model suggested that the top five important markers for predicting chronic cough were SII, smoking, NHHR, BMI, and SIRI. Conclusion This investigation discovered that NHHR was positively associated with chronic cough. Regular NHHR monitoring may serve as a potential tool for identifying individuals at higher risk of chronic cough.